Studi Perbandingan Penggunaan Aizuchi dalam Bahasa Indonesia dan Bahasa Jepang : Percakapan pada Situasi Pertemuan Pertama - Bembi Mulia Ramadhani; Aji Yudistira; Ishaura Anaya (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2023)
This study focuses on the difference in verbal aizuchi Indonesian in the frequency of use and timing in the first meeting between two people. The research method is qualitative and quantitative, by looking at aizuchi that occurs in online conversations using zoom. The quantitative method looks at the frequency of use and the variety of aizuchi used in conversation. The qualitative method looks at timings and their relationships in communication styles in Indonesian and Japanese cultures. The results of this study are:(1) The frequency of aizuchi in Japanese conversations is more significant than in conversations in Indonesian. (2) The timing of aizuchi in this conversation between Indonesian and Japanese is no different. The timing of the pronunciation of aizuchi in the conversation is hatsuwa tochuu refers to the overlapping or simultaneous utterance of aizuchi during a speaker's statement. The listener's response overlaps with the speaker's speech or when the speaker has not ended the speech. (3) As a result of the timing aizuchi taught by the speaker of this bilingual conversation, it can be concluded that the communication style of Indonesian and Japanese is the same, "共話" (kyowa) is a communication style in which the speaker intentionally pauses to wait for a response or "aizuchi" from the listener.Keywords - Aizuchi, frequency, timing, first meeting, online conversation.